Medical and Dietary Uses of N-Acetylcysteine - Špela Šalamon; Barbara Kramar; Tinkara Pirc Marolt; Borut Poljšak; Irina Milisav (MDPI AG, 2019)
N-acetylcysteine (NAC), a plant antioxidant naturally found in onion, is a precursor to glutathione. It has been used as a drug since the 1960s and is listed on the World Health Organization (WHO) Model List of Essential Medicines as an antidote in poisonings. There are numerous other uses or proposed uses in medicine that are still in preclinical and clinical investigations. NAC is also used in food supplements and cosmetics. Despite its abundant use, there are projections that the NAC global market will grow in the next five years; therefore, the purpose of this work is to provide a balanced view of further uses of NAC as a dietary supplement. Although NAC is considered a safe substance, the results among clinical trials are sometimes controversial or incomplete, like for many other antioxidants. More clinical trials are underway that will improve our understanding of NAC applicability.